LEGAL REVIEW OF WITHDRAWALS OF ROYALTIES BY COPYRIGHT MANAGEMENT INSTITUTIONS AND FOUNDATION OF COPYRIGHT INDONESIA BY ACCORDING TO LAW NUMBER 28 OF 2014 ON COPYRIGHT INSTITUTIONS - Ardil Anzani; Ma’ruf Hafidz; Hasbuddin Khalid (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal